Constitutional Rights Conflict in Child Marriage: Prioritizing the Right to Child Development Over the Right to Form a Family - Fauzan Al Gifar; Zulayka Muchtar (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2026)
This article presents a conflict of constitutional rights over child marriage in Indonesia, more specifically the tension between the right to establish a family through lawful marriage (Article 28B(1) of 1945 Constitution of Republic of Indonesia) and the right of children to their life, growth, development and protection from violence and discrimination (Article 28B(2)). The conducting of this study uses a normative juridical method, in which the sources of law used were statute, concepts and case laws. The judgment states that the right to marry and found a family is not absolute, but rather subject to legitimate restrictions under article 28J(2) of the Constitution and thereby upholds the children’s perspective to rights applying in accordance with the best interests of the child principle. While the minimum age for marriage now stands equally at 19 years for both sexes, the marriage dispensation procedure may contradict child protection aims and give rise to legal uncertainty particularly in light of disharmonising regulations with the child protection system when being applied with a soft touch.